HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI KUTABUMI IV KABUPATEN TANGERANG - Ajeng Nida Nisrina; Candra Puspita Rini; Nur Latifah (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
The purpose of this study was to determine whether the relationship of emotional intelligence could affect the achievement of the mathematics learning of fourth graders in SD Negeri Kutabumi IV Tangerang District. This research is a type of survey research with correlation technique. Samples studied were 34 respondents who are thestudents of grade IV-C at SD Negeri Kutabumi IV Tangerang District. The data of emotional intelligence (X) was obtained through a questionnaire consisting of 26 items and the data of mathematics learning achievement (Y) collected through the score recorded from the UAS (Final Exam) grades. The results of this study showed that there is a positive and significant relationship between emotional intelligence and the learning achievement of Mathematics with a correlation of 0,580 and with the regression equation Ã = 4,55 + 0,74X and the coefficient of determination of 0,3364 which means that emotional intelligence has a contribution of 33,64% towards the achievement of the mathematics learning.